2007
DOI: 10.1590/s0102-05362007000100003
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de feijão-vagem arbustivo, sob cultivo orgânico em duas épocas

Abstract: Seis genótipos de feijão-vagem arbustivo foram avaliados em Anápolis-GO, sob sistema orgânico de produção, nos períodos de outono-inverno (2002) e primavera-verão (2002/2003). Avaliou-se a precocidade, produtividade de vagens, peso e número de vagens por planta, total e comercial, peso e número de vagens com defeito (%), produtividade e peso de 100 sementes. O delineamento experimental utilizado foi de blocos ao acaso, com seis tratamentos (linhagens Hab 1, Hab 19, Hab 39, Hab 46, e as cultivares Coralina e Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
9
3
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 2 publications
8
9
3
1
Order By: Relevance
“…For bushing snap beans, Moreira et al (2009) observed a lower number of pods per plant, considering the averages of this study, for the conventional system, ranging from 2.2 to 7.1 pods per plant. In contrast, Vidal et al (2007), using the organic system during autumn-winter, reported values of between 9.5 and 14.1 for the average pods per plant, similar to those obtained in this study.…”
supporting
confidence: 88%
See 4 more Smart Citations
“…For bushing snap beans, Moreira et al (2009) observed a lower number of pods per plant, considering the averages of this study, for the conventional system, ranging from 2.2 to 7.1 pods per plant. In contrast, Vidal et al (2007), using the organic system during autumn-winter, reported values of between 9.5 and 14.1 for the average pods per plant, similar to those obtained in this study.…”
supporting
confidence: 88%
“…*Significant at 5%, **Significant at 1%, ns Not significant. The average pod mass values are lower than those obtained by Vidal et al (2007) in organic farming. However, it should be emphasized that the environment and genotypes evaluated by these authors were not the same as those evaluated in the present study, and the differences in these values are certainly related to the association between genetic and environmental effects, which influences the time required for the genotypes to reach the harvest point.…”
contrasting
confidence: 73%
See 3 more Smart Citations